What Evolutionary Biologists Can Learn from Artificial Life - Elena Fito, Santiago (My University, 2019)
Big questions in Evolutionary Biology and experimental limitations - The evolution of complex traits. - The role of neutral variation in adaptive evolution. - Selection for fitness vs selection for robustness. - The topography of adaptive landscapes and the evolution of landscapes. - Eco-evolutionary dynamics: how evolution changes ecology and how ecology modulates evolution. - Evolution of phenotype-genotype maps. - The evolution of genetic systems (sex, speciation, genome architecture). The advantages of microbial Experimental Evolution - They are easy to propagate and enumerate. - They reproduce quickly, which allows experiments to run for many generations. - They allow large populations in small spaces, which facilitates experimental replication. -They can be stored in suspended animation and later revived, which allows the direct comparison of ancestral and evolved types. -Many microbes reproduce asexually and the resulting clonality enhances the precision of experimental replication. -Asexuality also maintains linkage between a genetic marker and the genomic background into which it is placed, which facilitates fitness measurements. -It is easy to manipulate environmental variables, such as resources, as well as the genetic composition of founding populations. - There are abundant molecular and genomic data for many species, as well as techniques for their precise genetic analysis and manipulation.
Keywords: Biología; Evolución; Bioinformática; Evolutionary; Biology; Bioinformatics